Um estudo de caso sobre o estágio curricular supervisionado na licenciatura em Ciências Biológicas : possibilidades e limites na Universidade do Estado de Mato Grosso - Gattass, Leila Valderes Souza (2016)
This research regards the contribution of Supervised Internship when it comes to the foundation of teaching skills applied to Biological Sciences. Two main steps were developed. The first one deals with an analysis concerning guiding documents which manage the course itself, such as the Pedagogical Project and the Internship’s program. Hence, it is possible to comprehend its organization and operation, considering both formal and informal teaching environments. The second one has open-based interviews that include six students from the first class of Biological Sciences’ course, which is a distance learning one that provides licentiate degree (DEAD, UNEMAT). The interview’s questions were related to the activities developed by the students during the Supervised Internship, which is considered to have a key contribution to anchor the required knowledge toward consistent teaching abilities. Through a case study including a participant observation, there were accomplished both theoretical and practical studies upon necessary elements to build knowledge and skill, thanks to educational activities provided by Supervised Internship. The structure of the theoretical part of the study was developed considering the internship and its role as a former process of the professional knowledge regarding the licentiate degree in Biological Sciences. Our analysis supports on the formation, elaboration and transformation of the indispensable knowledge to the teaching’s professionalization. The main ideas of this work are organized in five chapters and they deal specifically with the role of the Supervised Internship in Biological Sciences focused on the teaching formation, as well as the knowledge’s construction through activities developed during the internship. Furthermore, it was also considered challenges, limits and possibilities to formative courses. To accomplish these aspects, formal and informal learning environments such as schools, parks or even rural communities were chosen as our scenarios. The formation and conception of needful knowledge in pedagogical contexts, associated with the establishment of helpful partnerships, provides conceptual and significant elements regarding the conception of educational activities. In addition, it is believed that an evaluation’s Project towards improving both theory and practice (know how) is also important for taking correct action on daily practice. Formation, conception and evaluation of knowledge and established partnerships are elements which work together in attempt to hold up a new time and environment to support knowledge and teaching abilities.